Percepción del personal médico que labora en el hospital Virgen de la Puerta – ESSALUD, La Esperanza julio 2017 sobre clima organizacional - Castro Ramírez, Carlos Eduardo (2018)
The general objective of this research is to determine the levels in each dimension with respect to the organizational climate of the medical personnel that work in the Virgen de la Puerta Hospital - EsSalud, La Esperanza, July 2017. This research is of the applied type and with a transversal cut, since the data collection occurred in a single moment and with unique time. The sample consists of 90 doctors who work at the Virgen de la Puerta Hospital in "La Esperanza". To obtain a diagnosis about the perception of the medical personnel, a questionnaire was applied to evaluate the characteristics of the personnel, the dimensions of the organizational climate: Sex, age, level of studies, specialty, work condition and time of service in EsSalud._x000D_ The purpose of this thesis is the measurement of organizational climate through the perception of medical personnel globally and at the level of dimensions such as leadership motivation, decision making, identity, communication, structure, innovation, conflict and cooperation and ultimately reward; This research is born from the need to know at what level the organizational climate is located._x000D_ The following conclusions are reached after analyzing the results, that there is a Good Organizational Climate perceived by 60 physicians that represents 66.7% of the total of the sample and with respect to the dimensions a Good level was found in the dimensions of Motivation, Leadership, Decision making, Identity, Communication, Structure, Innovation and Conflict-cooperation with the exception of the Reward dimension that presents a Regular level; However, in all dimensions a close and highly significant association with the Organizational Climate was found